The legacy of Gildas constructions of authority in the early medieval West - Joyce, Stephen J. ca. 20./21. Jh (The Boydell Press, 2022)
A provocative new investigation into the shadowy figure of Gildas, his influence and representation
Title from publisher's bibliographic system (viewed on 14 Jul 2022)
Keywords: Gildas / 516?-570?; Gildas / 516?-570? / Influence; Gildas -- Sapiens -- 504-570; Christian saints / Biography